Efeitos do cloridrato de metformina sobre atividade da colinesterase, sistema antioxidante e ação mutagênica em Danio rerio (cypriniformes: cyprinidae) - Demarco, Natani Ribeiro (2019)
Metformin hydrochloride is a medicine used primarily in the treatment of Diabetes Mellitus, a chemical compound derived from guanidine. This chemical is partially metabolized in the human organism and eliminated by urine, being incorporated into aquatic environments without its due bioremediation. In view of this fact, as well as the limited knowledge about the potential mutagenic, cholinergic and antioxidant effects of metformin hydrochloride, the objective of this study was to evaluate the effects of metformin hydrochloride on the antioxidant and cholinergic systems, as well as its mutagenic potential of the bioindicator Danio rerio. The experimental procedures presented here were approved by the Animal Use Ethics Committee (AUEC-Unioeste). The animals were acclimatized at temperature (24 + 1°C), pH (7.0 + 0.5) and oxygenation (5.0 + 0.5) constants, for a period of seven days. Then, in a completely randomized design, the fishes were separated into six groups exposed to the different concentrations of metformin hydrochloride for the determination of the LC50 and acute effect of the drug for a period of 96 hours. Then, after determining the non-lethal concentration of 0.45 g / L, six other groups (n = 10 per group) were separated: four groups for evaluation of the chronic effect of metformin hydrochloride euthanasia at different times (15, 30, 45 and 60 days), a negative control group and a positive control group (treated with cyclophosphamide). At the end of the experimental periods, the animals were anesthetized in eugenol (30 mg / L) and the biological materials (muscle and blood) were removed. In the muscular matrix, the action of the drug on the antioxidant system (Superoxide dismutase - SOD, Catalase - CAT, Lipoperoxidation - LPO and Glutathione transferase - GST), cholinesterase enzyme activity (ChE) and mutagenic Micronucleus Test - MN). It was noticed that during chronic exposure to metformin hydrochloride, in 15 days of treatment the animals had cytotoxic effects showing levels of necrosis in their erythrocytes. Activations of the antioxidant system were also observed, with elevation of the enzymatic activity of SOD, CAT and GST. Throughout the experimental period (30, 45 and 60 days), chronic effects were observed with elevation of MN frequency, as well as activation of repair systems, such as programmed cell death. Demonstrating the potential antioxidant and mutagenic effects triggered by the drug. Believing to treat a period of adaptation to the use of metformin.